THE FUTURE OF ARTIFICIAL INTELLIGENCE IN TRANSLATION AND ITS SOCIETAL IMPLICATIONSTHE FUTURE OF ARTIFICIAL INTELLIGENCE IN TRANSLATION AND ITS SOCIETAL IMPLICATIONS - Raimov Lazizjon Alisherovich (Scholar Express Journal, 2025)
The rapid advancement of artificial intelligence (AI) in translation has significantly transformed global communication, reducing linguistic barriers and enhancing cross-cultural interactions. Neural Machine Translation (NMT) and deep learning techniques have enabled AI to provide more accurate and context-aware translations, benefiting fields such as international relations, education, and business. However, challenges remain, including linguistic diversity preservation, contextual accuracy, and ethical concerns such as algorithmic bias and data privacy. This article explores the evolving role of AI in translation, its societal implications, and the need for interdisciplinary collaboration to ensure inclusive and responsible technological development
Keywords: Artificial intelligence; machine translation; neural machine translation